Dirty Hands, Supreme Emergencies, and Catholic Moral Theology. Issue 4 (1st February 2022) - Sandsmark, Evan
Abstract: Is it ever permissible to commit an intrinsically evil act in order to avert catastrophe? Consequentialists say yes, denying the very concept of intrinsic evil, since the action that leads to the best consequences is by definition right. Moral absolutism, in contrast, insists that it is never permissible to commit an action that is inherently evil, regardless of the consequences. However, there is a middle position, occupied by "dirty hands" theorists, who claim that actions can be both necessary and immoral. I argue that Catholic moral theology, although generally associated with moral absolutism, can and should make conceptual space for the idea of dirty hands, both because it saves the Church from committing itself to what seem to be moral absurdities and because the phenomenon of dirty hands captures a genuine dimension of our moral experience in a fallen world.